Optimisation of palm kernel shell activated carbon for methylene blue adsorption: taguchi approach and Isotherm study / Muhammad Nazrin Sabudi - Sabudi, Muhammad Nazrin; Amir Hamzah, Siti Nur Azira; Yazid, Nur Anisah; Mohammad Misroji, Nurul Husna
Abstract-Activated carbon was used for methylene blue or dye adsorption in liquid solution analysis. Taguchi orthogonal array design was employed to optimize the process parameters for preparation of activated carbon. The influence of process parameters; impregnation ratio, activation temperature and activation time were studied. Based on the S/N ratio analysis, the optimized conditions are the impregnation ratio of 0.6, the activation temperature of 750C and the activation time of 90 min considering the condition larger is the better approach. Analysis of Variance (ANOVA) is applied and proved that the most influential factor on the methylene blue adsorption is impregnation ratio. From the result, the linear regression model was developed and the value of R2 is 0.9625. This shows that, the regression was 96.25 % reliable to the experimental value. As for isotherm study, it is shown that the optimum condition of the methylene blue adsorption on activated carbon follows the Langmuir model. It is because the value of regression coefficient, R2 for Langmuir model is the highest among all models (R2=0.9987), where the Freundlich model is R2=0.9834 and the Temkin model is R2=0.9957.